The theme of Jewish persecution of Christians in the Gospel according to St. Matthew - Hare, Douglas R. (Society for New Testament Studies monograph series, 1967)
It has long been recognized that in the Gospel according to St Matthew the conflict between Jesus and the Pharisees has been intensified and it has often been suggested that this intensification reflects the continued struggle between the Church and the synagogue. The theme of Jewish persecution of Christians in the Gospel according to St Matthew is examined in this book with two questions in mind: 1. Has Matthew exaggerated the severity of the persecution? 2. How has the persecution influenced Matthew's theology? Professor Hare examines the historical data relating to the suffering imposed upon the Christians and refers to Rabbinic literature and Christian sources other than Matthew in order to evaluate Matthew's portrayal of the persecutions. He concludes that persecution was directed primarily against Christian missionaries, not against rank-and-file Christians.